2016
DOI: 10.1242/dev.112672
|View full text |Cite
|
Sign up to set email alerts
|

Fox transcription factors: from development to disease

Abstract: Forkhead box (Fox) transcription factors are evolutionarily conserved in organisms ranging from yeast to humans. They regulate diverse biological processes both during development and throughout adult life. Mutations in many Fox genes are associated with human disease and, as such, various animal models have been generated to study the function of these transcription factors in mechanistic detail. In many cases, the absence of even a single Fox transcription factor is lethal. In this Primer, we provide an over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
286
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(289 citation statements)
references
References 174 publications
(189 reference statements)
3
286
0
Order By: Relevance
“…In accordance with its inhibitory function, FOXA1 was down‐regulated in NEC tissues and in mimic miR‐431‐overexpressing Caco‐2 cells. FOXA1, a winged‐helix transcription factor of the 44‐member FOX family, is known to play critical roles in the development and homeostasis of multiple tissues and facilitating the binding of many other transcription factors to their targets (27). A brief summary of the functions of FOXA1 is presented in Supplemental Table S5.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with its inhibitory function, FOXA1 was down‐regulated in NEC tissues and in mimic miR‐431‐overexpressing Caco‐2 cells. FOXA1, a winged‐helix transcription factor of the 44‐member FOX family, is known to play critical roles in the development and homeostasis of multiple tissues and facilitating the binding of many other transcription factors to their targets (27). A brief summary of the functions of FOXA1 is presented in Supplemental Table S5.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of β‐catenin signalling can further exert different biological effects by inducing the transcription of corresponding target genes. β‐catenin binds to T cell factor (TCF) to promote transdifferentiation and fibrosis and connects to foxhead frame transcription factor (Foxo) to promote anti‐inflammatory and wound repair response . Joo et al confirmed that sitagliptin can restore Foxo3a activity and reduce renal structural and functional impairment by reducing the ratio of P‐Foxo3a/total Foxo3a in 5/6 nephrectomy rats.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis of EWS‐FLI1‐binding peaks suggested possible cooperative binding with FOX family transcription factors. There are 44 members of the FOX family genes in human and mouse . Gene expression and functional analysis identified FOXQ1 as the FOX protein responsible for serving as a co‐binding partner of EWS‐FLI1.…”
Section: Discussionmentioning
confidence: 99%